FAKTOR LINGKUNGAN FISIK YANG BERHUBUNGAN DENGAN ANGKA KUMAN UDARA DI RUANG RAWAT INAP KELAS I, II, DAN III RST WIJAYAKUSUMA PURWOKERTO TAHUN 2018 - Citra Kusumawardhani U.P; Asep Tata Gunawan; Tri Cahyono (Buletin Keslingmas, 2019)
Hospital Is An Health Service Tool Which Is Possible Make A Healthcare Associated Infection (Hais) That Can Caused Of The Number Of Airborne Germs. Secondary Data Bacteriology Inspection Result Is point that the floor of 2nd class Srikandi Inpatient room is not full the condition, the result is 26 colony/cm2. The large of population is 67, while the large of sample is 35 sample. Analysis model that is used on this research is Rank Spearman. Data collection is done by measurement and observation. Mean of the measurement is, the number of airborne germs is 7871,43 CFU/m3, temperature is 27,35oC, humidity is 56,20%, lighting intensity is 154,63 lux, room density is 10,3 m2/TT. Analysis result for temperature and the number of airborne germs is p=0,465; (rho)=0,128, humidity with the number of airborne germs is p=0,828; (rho)=0,038, lighting intensity with the number of airborne germs is p=0,061; (rho)=0,320, density room with the number of airborne germs is p=0,885; (rho)=0,025, ventilation with the number of airborne germs is p=0,113; (rho)=0,273, means of air circulation with the number of airborne germs is p=0,636; (rho)=0,083.  All of factors of independent variable is not in significant relation with the number of airborne germs (p value 0,05). We recommend that routine desinfection every month to reduce the number of airborne germs